The Effect of Green Intellectual Capital on Sustainable Business Performance with Green Innovation as a Mediation in UMKM in Pematangsiantar City - Sisca; Pasaman Silaban; Fajar Rezeki Ananda Lubis (Universitas Muhammadiyah Surabaya, 2025)
This study is to test what is considered important in improving MSMEs in Pematangsiantar City. Data collection using quantitative methods with a sample of 300 people and then data processing using the Partial Least Square Structural Equation Model. The study's findings indicate that green innovation in MSMEs in Pematangsiantar City is significantly influenced by green human capital, green structural capital, and green relational capital. Furthermore, sustainable company performance is not much impacted by green human capital. In contrast, green relational and structural capital significantly affects the success of sustainable businesses. In the meanwhile, sustainable company performance is significantly impacted by green innovation. Additionally, the relationship between green human capital and sustainable company performance can be mediated by green innovation. The relationship between green structural capital and sustainable business performance in Pematangsiantar City's MSMEs can also be mediated by green innovation. Finally, green innovation can act as a mediator in the interaction between green relational capital and sustainable business performance in MSMEs in Pematangsiantar City.